ANALYZING THE TYPES OF SPEECH ACTS USED IN TEACHING-LEARNING INTERACTION - Widi Andewi Andewi; Winia Waziana; Wirathama Hazera Putra (English Language Education Department, Universitas Majalengka, 2022)
This qualitative study was aimed at analyzing the types of speech acts used in teaching-learning interaction. The participants of this study were one class of 10th grade students of SMAN 1 Bandar Lampung. In collecting the data, observation and audio-visual material were used. Then, descriptive analysis was used to analyze the speech acts used in teaching-learning interaction. The results of this study showed that the speech acts mostly used was directive speech acts. On the other hand, declarations speech acts was not used at all. In conclusion, since the role of the teacher is as an initiator and sustainer of the interaction in the classroom and regarding the opportunities for the full range of human interactions are limited which make the students get more difficulties in acquiring appropriate language use patterns, therefore, directives speech acts is appropriate, used in classroom interaction context to help the students to acquire the target language in the comprehension input and lead them to have positive behavior for learning. Keywords: speech acts, teaching-learning interaction.